More Methodologico, or Why is It Worth Knowing How? - Szynkiewicz, Mariusz (Sensus Historiae, 2023)
The article discusses selected issues of the contemporary information environment. These issues are considered from the perspective of the process of distributing scientific knowledge (using educational activities as an example). The paper presents theses regarding potential directions for reforming the philosophy of education and calls for the expansion and supplementation of teaching programs with education in the field of basic methodological and logical competencies, along with its justification.